Optimal Design of Minichannel Cold Plate for the Thermal Management of Cylindrical Battery Modules. Issue 4 (17th February 2023) - Ling, Lei; Li, Li; Xie, Yajun; Wang, Tianbo; Zheng, Keqing; Shan, Shuai; Zhang, Lanchun; Bei, Shaoyi; Xu, Qiang
Abstract : The application of the minichannel cold plate in a cylindrical battery module encounters the problem of poor heat transfer capability as it cannot match well with the curved surfaces of the cylindrical batteries. Herein, design optimization of a minichannel cold plate is performed to enhance its heat dissipation performance in the cylindrical battery module. In‐depth analyses are made on the thermal behavior of a cylindrical battery module with minichannel cold plates. Influences of different cold plate design parameters, including the size and position of the heat transfer interface between the batteries and the cold plates, the cold plate material, and the cold plate thickness, are examined and compared under various coolant velocities. The results highlight the significance of cold plate design in achieving a high‐performance cooling system for the cylindrical battery module. Based on the results, some general rules are set for the design of minichannel cold plates in the cylindrical battery module, which can provide useful guidance for the future development of minichannel cold plates. Abstract : In‐depth analyses are made on the thermal behavior of a cylindrical battery module with minichannel cold plates. Influences of different cold plate design parameters are examined and compared. Some general rules are set for the design of minichannel cold plates in the cylindrical battery module.